Effect of Mulberry Leaf Extracts on Color, Lipid Oxidation, Antioxidant Enzyme Activities and Oxidative Breakdown Products of Raw Ground Beef During Refrigerated Storage. Issue 3 (10th February 2016) - Zhang, Xinzhuang; Li, Deyong; Meng, Qingxiang; He, Cui; Ren, Liping
Abstract: The study investigated the effects of mulberry leaf extracts (MLE) on the color, lipid oxidation, antioxidant enzyme activities and oxidative breakdown products of raw ground beef during refrigerated storage. The five treatments were: MLE at 0, 100, 500 and 1, 000 μg/g muscle (C, low concentration mulberry leaves extracts (LM), medium concentration mulberry leaves extracts (MM) and high concentration mulberry leaves extracts (HM)) and positive control with 20 μg Vitamin E/g muscle (VE). MLE maintained color, reduced peroxide and thiobarbituric acid reactive substances values during storage ( P  < 0.05) with no effect on free thiol. MLE increased activities of superoxide dismutase and glutathione peroxidase at 312 h ( P  < 0.05). There were more phospholipids from the HM treatment than the control group ( P  < 0.05); unsaturated fatty acids and reducing sugars in the VE group were higher than the C group ( P  < 0.05). The results indicated that MLE could better use as natural antioxidants to maintain the meat quality, extend shelf‐life and prevent economic loss for food processing industry. In addition, one interesting finding was that the antioxidant mechanism of MLE was different comparing to VE during the different stages of lipid oxidation, which MLE worked at the first step and VE protected the second step when phospholipid was decomposed into unsaturated fatty acids. Therefore, we could conclude that it would be better to combine the MLE and VE to protect the meat quality during refrigerated storage. Practical Applications: Mulberry leaves were rich in alkaloids, polyphenols, flavonoids and anthocyanins, which could be responsible for health benefits as well as herbal medicine for many years in various cultures. Some studies had found that MLE had the antioxidant activities. However, scientific information about the antioxidant properties of MLE in meat and their influence on meat quality is still scarce. The results indicate that MLE have the antioxidant activity, helping maintain the meat color, inhibiting lipid oxidant and enhancing antioxidant enzyme activity. In addition, the antioxidant mechanism of MLE protected phospholipids from oxidation and VE mainly protected the unsaturated fatty acids and reducing sugars. This research explains the antioxidant mechanism of MLE could better use as natural antioxidants to maintain the meat quality, extend shelf‐life and prevent economic loss for food processing industry.